2014
DOI: 10.1007/s10113-014-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural disasters and land-use/land-cover change in the southwest coastal areas of Bangladesh

Abstract: Natural hazards and major land-use/land-cover change can have significant impacts on humans around the world. If these two concerns exist together in a coastal area, the consequences for people and the environment may be severe. This study investigated the combined effects of land-use changes and natural disasters in the southwest coastal area of Bangladesh. Satellite images were analyzed to detect changes in land cover in the study period of 13 years (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…Since times past, rice fields are the most dominant land in the rural villages of coastal districts. However, due to high profits from shrimp and salt farming, the rice fields are changing to another use [47][48][49][50]. Shrimp farming has affected around 1 million ha of arable land in the southern coastal area [51].…”
Section: Agricultural Landmentioning
confidence: 99%
See 2 more Smart Citations
“…Since times past, rice fields are the most dominant land in the rural villages of coastal districts. However, due to high profits from shrimp and salt farming, the rice fields are changing to another use [47][48][49][50]. Shrimp farming has affected around 1 million ha of arable land in the southern coastal area [51].…”
Section: Agricultural Landmentioning
confidence: 99%
“…Billah and Ramhan (2004) have examined the mangrove forests using satellite imagery and found that the largest area occupied by the vegetation was 48.59% in Khulna city. However, due to natural and anthropogenic causes, all vegetation cover has been declining and converted to other land categories [15,50,52,[91][92][93]. A spatio-temporal analysis of satellite images using Normalized Difference Vegetation Index (NDVI) datasets showed that the mangrove forest decreased 15.47% between 1989 and 2010 [94].…”
Section: Forest Covermentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the BWDB in 1995-96 came up with the US dollar 62m million Asian Development Bank (Khan et al, 2015)  Comments-as work on Gorai Restoration has remained suspended after the experimental dredging during two seasons, the large amounts spent on the project have become totally unproductive. with the concepts of soil less agriculture.…”
Section: Khulna Jessore Drainage Rehabilitation Projectmentioning
confidence: 99%
“…7 One noted that the increase in salinity could also be related to the level of water in the river at high tide being higher than the level of arable land due to the effects of sediment accumulation on the floor of the riverbed (this following an engineering fault in the construction of the embankment along the coast). It has also been reported that climatic events (sea-level rise, storm surges, tidal flooding, and droughts) and anthropogenic factors (decreasing upstream flow, siltation in the riverbed, shrimp culture, and the construction of the Farakka Barrage in India and coastal embankments in Bangladesh) had increased the vulnerability to higher levels of salinity in the southwestern coastal region (Pouliotte et al 2009;SRDI 2012;Habiba et al 2014;Khan et al 2014;Saroar 2014). …”
Section: Household Perceptions Of and Adaptation To Changes In Climatmentioning
confidence: 99%